Variance anisotropy in compressible 3‐D MHD. Issue 6 (28th June 2016) - Oughton, S.; Matthaeus, W. H.; Wan, Minping; Parashar, Tulasi
Abstract: We employ spectral method numerical simulations to examine the dynamical development of anisotropy of the variance, or polarization, of the magnetic and velocity field in compressible magnetohydrodynamic (MHD) turbulence. Both variance anisotropy and spectral anisotropy emerge under influence of a large‐scale mean magnetic field B 0 ; these are distinct effects, although sometimes related. Here we examine the appearance of variance parallel to B 0, when starting from a highly anisotropic state. The discussion is based on a turbulence theoretic approach rather than a wave perspective. We find that parallel variance emerges over several characteristic nonlinear times, often attaining a quasi‐steady level that depends on plasma beta. Consistency with solar wind observations seems to occur when the initial state is dominated by quasi‐two‐dimensional fluctuations. Key Points: Parallel variances are robustly generated in compressible MHD turbulence, even when absent initially They are usually a minority of the fluctuation energy Perpendicular and parallel variances are not independent